2004
DOI: 10.1063/1.1648635
|View full text |Cite
|
Sign up to set email alerts
|

A study on the anisole–water complex by molecular beam–electronic spectroscopy and molecular mechanics calculations

Abstract: An experimental and theoretical study is made on the anisole-water complex. It is the first van der Waals complex studied by high resolution electronic spectroscopy in which the water is seen acting as an acid. Vibronically and rotationally resolved electronic spectroscopy experiments and molecular mechanics calculations are used to elucidate the structure of the complex in the ground and first electronic excited state. Some internal dynamics in the system is revealed by high resolution spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 36 publications
3
75
1
Order By: Relevance
“…A similar analysis, based on very limited spectroscopic data, namely the comparison of experimental and theoretical OH vibrational frequencies, lead to an incorrect proposal of a non planar equilibrium structure for the anisole-water complex 151 . This was corrected by high-resolution laser induced fluorescence spectroscopy (LIF) measurements of the rotational constants, which showed that water is located in the anisole symmetry plane and is bound to the molecule by a conventional hydrogen bond 152 and further confirmed by experimental [153][154][155] and computational 155,156 findings. As a consequence, for a proper benchmark reference it is necessary to combine structure identification of the complexes (by means, e.g., of rotational spectra) with an analysis of the vibrational transitions.…”
Section: Vibrational Properties-unfortunatelymentioning
confidence: 97%
“…A similar analysis, based on very limited spectroscopic data, namely the comparison of experimental and theoretical OH vibrational frequencies, lead to an incorrect proposal of a non planar equilibrium structure for the anisole-water complex 151 . This was corrected by high-resolution laser induced fluorescence spectroscopy (LIF) measurements of the rotational constants, which showed that water is located in the anisole symmetry plane and is bound to the molecule by a conventional hydrogen bond 152 and further confirmed by experimental [153][154][155] and computational 155,156 findings. As a consequence, for a proper benchmark reference it is necessary to combine structure identification of the complexes (by means, e.g., of rotational spectra) with an analysis of the vibrational transitions.…”
Section: Vibrational Properties-unfortunatelymentioning
confidence: 97%
“…[10] In the second the authors suggest a conformation of the complex with the water oxygen atom coplanar to the ring based on the results of vibronically and rotationally resolved spectroscopy and molecular-mechanics calculations. [11] We measured the molecular-beam Fourier transform microwave spectra of six isotopomers of ANI···water, namely, ANI···H 2 O, ANI···D 2 O, ANI···DOH, ANI···H 2 18 O, ANI···D 2 18 O, and ANI···D 18 OH. We first assigned the rotational spectrum of the normal species, ANI···H 2 O.…”
mentioning
confidence: 99%
“…2943.058 (2) [c] 2943.578 (2) [a] The rotational constants for the normal species from reference [11] predict the positions of the hydrogen atoms of the water molecule. Since the statistical weight indicates that they are equivalent to one other, we assumed that they point towards the oxygen atom of anisole, thus forming a bifurcated H bond.…”
mentioning
confidence: 99%
“…The TOF mass spectrometer is a commercial model (RM Jordan, reflectron TOF mass spectrometer), whereas that used for velocity mapping ion/electron imaging is home built; both have been described elsewhere. 15,30 The molecular beam containing the anisole-carbon dioxide complexes was formed by using standard methods, i.e. the adiabatic expansion of a gas mixture containing all the relevant chemical species and a carrier gas.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…One hydrogen from water pointing toward the electron lone pairs on the anisole oxygen atom and the water center of mass lying on the anisole symmetry plane, a partial involvement of the p-electronic system with the second hydrogen atom from water occurs, more relevant in the electronic excited state. [15][16][17] It has been a Dipartimento di Chimica 'Ugo Schiff', Università degli Studi di Firenze, demonstrated that the anisole-methanol complex is also hydrogen bonded, even if theoretical modeling suggests that the interaction of methanol with the aromatic system should be quite important. 18 The anisole-ammonia complex is stabilized by many contact points between the two moieties as the ammonia is placed above the anisole aromatic system, displaced towards the methoxy group.…”
Section: Introductionmentioning
confidence: 99%